ANTIPYRETIC ACTIVITY OF ETHANOL AND AQUEOUS EXTRACT OF ROOT OF ASPARAGUS RACEMOSUS IN YEAST INDUCED PYREXIA - P.A , VASUNDRA DEVI; s, DIVYA PRIYA (Asian Journal of Pharmaceutical and Clinical Research, 2013)
ABSTRACT Objective: To evaluate and compare the in vivo antipyretic activity of the aqueous and the ethanol extract of root of Asparagus racemosus. Methods: The presence of phytochemicals like flavonoids and saponins were identified by TLC and the invivo antipyretic activity was determined by brewer's yeast induced pyrexia method. Results: The results showed that the ethanol extract of root of Asparagus racemosus possessed significant antipyretic effect compared to the aqueous extract which may be attributed to the presence of flavonoids and saponins in the extracts whose presence were observed in TLC. Conclusion: This study provides evidences for the antipyretic activity of Asparagus racemosus which could partly contribute to its ethno medical use. Â Key Words: Asparagus racemosus, Antipyretic effect, flavonoids ,saponins, TLC